The Stock Price Effect of Risky Versus Safe Debt - Shyam-Sunder, Lakshmi (Journal of Financial and Quantitative Analysis, 1991)
This paper tests whether there is a difference in the stock price reactions to industrial straight debt offerings of different risk. Using bond ratings at the time of announcement as a measure of risk, we find that there is no monotonic relation between stock price impact and rating and no statistically significant difference across risk classes, even though the sample includes low-rated debt issues from recent years. This confirms earlier evidence on straight debt issues, but differs from the evidence on convertible securities. The paper also finds that the results for straight debt are not affected by shelf registrations or by the issuing firms' involvement in merger and acquisition-related activity.